Communication Planning Model of the Office of Culture and Tourism in Marketing Islamic Tourist Attractions in Banda Aceh City - Budiman Purba; Afriadi Amin; Abdul Karim Batubara; M. Fachri Setiawan Hartono (Lembaga Bale Literasi, 2026)
This study aims to examine the communication planning model employed by the Office of Culture and Tourism in marketing Islamic tourist attractions in Banda Aceh. The theoretical framework draws upon concepts of communication planning, marketing, and tourism. The Communication Planning Models of Assifi and French, Middleton, and the P-Process model serve as analytical references in addressing the research objectives. This research adopts a qualitative approach with a case study design. The findings reveal that the communication planning model utilized by the Office of Culture and Tourism in promoting Islamic tourism in Banda Aceh incorporates key elements from the Assifi and French, Middleton, and P-Process models. However, several differences emerge in the planning stages, particularly in problem identification and formulation, as well as audience segmentation. The study also identifies challenges in measuring the effectiveness of the communication plan, especially when relying solely on the number of tourist arrivals as an indicator. Tourism marketing targets are not consistently oriented toward achieving the expected visitor numbers. Instead, the primary focus of marketing efforts lies in introducing and promoting the potential of Islamic tourist attractions in Banda Aceh.